SOCIAL, ECONOMIC AND PERSONAL ISSUES OF FISHER WOMEN IN COASTAL VILLAGES OF THOOTHUKUDI DISTRICT - S.Veniswari, Research Scholar, Dr. B. Revathy, Professor & Head (International Journal of Advanced Science and Technology, 2020)
Fisher women play an important role in coastal economic activities. Fisher women are activelyinvolved in input and output markets as well as in supporting markets for fishing activities. Womenplay an all-important role in the marine fishery by involving in harvesting, processing and marketingof fish. This study is based on primary as well as secondary data. The primary data were collectedfrom the fisher women in coastal area of Thoothukudi district. For collecting the primary data,proportionate random sampling technique was used. The Thoothukudi district constitutes theuniverse. The fishing villages in this district are the stratus. The number of fisher women is theprimary and ultimate units of the sample respectively. By employing random sampling technique 200respondents were selected from five villages. From each village 40 fisher women were selected.Fisher women in the study area are playing double roles in the development of the society. In afishermen family, the responsibility of house hold management and the responsibility of getting andrepaying debts will be mainly on the women shoulders. Most of them are earning members andengaged in fishery activities. But their life standard is very poor when compared with other women inIndia. So prior recognition should be given for the development of fisher women.